2015
DOI: 10.4143/crt.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Chondrosarcoma: A Single Institutional Experience

Abstract: PurposeThe prognostic factors of chondrosarcoma remain uncertain as only a few large studies with long-term follow-up have been reported. The aim of this study was to analyze oncological outcomes and prognostic factors.Materials and MethodsA retrospective review of oncological outcomes and prognostic factors was performed on 125 consecutive chondrosarcoma patients who underwent surgery at our institution.ResultsOverall survival was 91.6%±2.5%, 84.1%±3.8%, and 84.1%±3.8% at 5, 10, and 15 years respectively. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 22 publications
2
33
2
1
Order By: Relevance
“…Our results show, that MD is more common in G2/3 lesions as described by others [9, 34, 39, 41] but it is independent from surgical margins with the same rate of MD in R0 and R1 resected patients, and also independent from LR. This is in some respect in contrast to the literature [9, 10, 35] but other authors did see the same, confirming grade and location [42] as risk factors or grade as the only significant risk factor [16] for MD in multivariate analyses. In a large survey in Finland [36] the decade of diagnosis was the only significant factor on MD with an increased risk in the 1980s.…”
Section: Discussionmentioning
confidence: 41%
“…Our results show, that MD is more common in G2/3 lesions as described by others [9, 34, 39, 41] but it is independent from surgical margins with the same rate of MD in R0 and R1 resected patients, and also independent from LR. This is in some respect in contrast to the literature [9, 10, 35] but other authors did see the same, confirming grade and location [42] as risk factors or grade as the only significant risk factor [16] for MD in multivariate analyses. In a large survey in Finland [36] the decade of diagnosis was the only significant factor on MD with an increased risk in the 1980s.…”
Section: Discussionmentioning
confidence: 41%
“…Previous studies have found that high-grade chondrosarcomas of the axial skeleton have significantly worse long-term (at 10 years and beyond) conditional survival compared with high-grade disease of the extremity which further underscores this point. 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Although our followup is short, we found no instances of local recurrence in our five patients. Bindiganavile et al [4] stated that the overall survival of chondrosarcoma was 91.6%, 84.1%, and 84.1% at 5, 10, and 15 years, respectively. The high histologic grade and axial location were the two negative outcome predictors.…”
Section: Discussionmentioning
confidence: 99%